Translation in Europe during the Middle Ages - Borsari, Elisa 1979- (Peter Lang, 2020)
The Latin-Greek glosses are a product of translation and a source of the Romance languages. This study provides an overview of translation into European languages (French, English, German, Castilian, Portuguese, Catalan and Italian) during Middle Ages, by prestigious academic researchers.